Use of comprehensive two-dimensional gas chromatography to evaluate the shelf life of soybean oil, its effect in the manufacture of biodiesel - Salazar Mogollón, Noroska Gabriela (2017)
The study aimed to determine the differentiation of biodiesel prepared from regular and aged soybean oils, through acomprehensive two-dimensional gas chromatography, combined with a main component analysis (PCA), as well as toidentify the compounds present in both raw materials. In order to evaluate the samples in the 2D system, three secondarystationary phases were established: SBL-IL61, Supelcowax and HP-50. Results showed that only polar secondary coating,SBL-IL61, was able to perceive a crucial difference between the samples. The largest difference was observed in theidentification of the highest concentration of polyunsaturated fatty acid methyl ester (FAME) in aged soybean biodiesel,such as C20: 4n-6, C20: 5n-3, C20: 3 and C21: 5. These compounds are quite prone to oxidation, which would lead todevaluation of biodiesel as a final product, thus may be used as markers for biodiesel degradation. In consequence, ananalytical technique that provides increased detection of these biodiesel quality-dependent compounds is recommended.Keywords: biodiesel, comprehensive two-dimensional gas chromatography (GC×GC), multiway principal component